Hyperbolic dynamics and Brownian motion an introduction - Franchi, Jacques; Le Jan, Y. (Yves), 1952- (Oxford : Oxford University Press, 2012)
An introduction to several important fields of modern mathematics. The exposition is based on an interplay between hyperbolic geometry, stochastic calculus, special relativity and chaotic dynamics. It is suitable for anyone with some solid background in linear algebra, calculus, and probability theory.
Includes bibliographical references and index.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Differentiable dynamical systems; Geometry, Hyperbolic; Brownian motion processes